Contracts as Trust Substitutes in Collaborative Business. - Arenas, Alvaro; Wilson, Michael (Computer (00189162), 2008)
The article offers advice to corporate information technology officers on managing collaboration between computer systems as a result of mergers and acquisitions of different companies. Distributed computing through service-oriented architecture is one solution to the problem of interoperability. The creation of service-level agreements between the managers of the separate systems, and means of monitoring compliance automatically are examined.